Microwave spectroscopy on heavy‐fermion systems: Probing the dynamics of charges and magnetic moments. Issue 3 (19th February 2013) - Scheffler, Marc; Schlegel, Katrin; Clauss, Conrad; Hafner, Daniel; Fella, Christian; Dressel, Martin; Jourdan, Martin; Sichelschmidt, Jörg; Krellner, Cornelius; Geibel, Christoph; Steglich, Frank
Abstract Investigating solids with light gives direct access to charge dynamics, electronic and magnetic excitations. For heavy fermions, one has to adjust the frequency of the probing light to the small characteristic energy scales, leading to spectroscopy with microwaves. We review general concepts of the frequency‐dependent conductivity of heavy fermions, including the slow Drude relaxation and the transition to a superconducting state, which we also demonstrate with experimental data taken on UPd2Al3. We discuss the optical response of a Fermi liquid and how it might be observed in heavy fermions. Microwave studies with focus on quantum criticality in heavy fermions concern the charge response, but also the magnetic moments can be addressed via electron spin resonance (ESR). We discuss the case of YbRh2Si2, the open questions concerning ESR of heavy fermions, and how these might be addressed in the future. This includes an overview of the presently available experimental techniques for microwave studies on heavy fermions, with a focus on broadband studies using the Corbino approach and on planar superconducting resonators.